Health Communication Strategy of Karawang Regency Government Through EMAS Program in Order to Decrease Mother Mortality and Infant Mortality Rate in Karawang Regency - Nursanti, Siti; Dida, Susane; Hidayat, Mien; Afriandi, Irvan (International Journal of Engineering and Technology, 2018)
Maternal mortality and infant mortality rate is one of the benchmarks of the health status of a region. The inability Maternal mortality and infant mortality rate is one of the benchmarks of the health status of a region. The inability of pregnant women and their immediate environment to recognize maternal signs in pregnant women and childbirth is one of the causes of maternal mortality and infant mortality. Karawang regency as one of the biggest contributor of Maternal Mortality Rate and Infant Mortality Rate in West Java, makes Expanding Maternal and Neonatal Survival or EMAS as one of strategy to decrease Mortality Rate and Infant Death. USAID EMAS Program started in 2013 and ended in 2016, and continued by West Java Provincial Health Office one of them in Karawang regency. This study aims to find out what are the communication strategies used by Karawang regency in order to reduce maternal and infant mortality rates and how to apply them in the community Karawang regency. This research uses constructivist paradigm with case study approach. The findings of this research are 1. The existence of an integrated program using communication technology with the name SiJariEMAS 2. The establishment of civil society forum consisting of all levels of society committed to supervise the health service to the public.Â Â